Implementation of the Group Investigation Cooperative Learning Model with Device Media in Indonesian Language Learning to Increase Student Activity in Class XI Science 4 State High School 1 Wajo - Ahmad Ghazali; Nurcaya; Jumadi; Muhlis (International Journal of Science and Society, 2022)
This study aims to increase student activity through the application of the group investigation cooperative learning model with gadget media in class XI Science 4 State High School 1 Wajo. This research is included in classroom follow-up research which refers to the CAR model by Kemmis, McTaggart, & Nixon which includes planning, implementing, observing and reflecting activities in each cycle. Action research in the form of Group Investigation syntax starting from identifying, grouping, investigation, organizing, and evaluating. The main data in the form of observations of student activity and syntax implementation. Data collection techniques with interview and documentation methods. Validation of data by triangulation method. Qualitative descriptive data analysis consists of three stages, namely data reduction, data presentation and conclusion drawing. The results showed that there was an increase in student activity during Indonesian language learning in class XI Science 4 State High School Wajo from Cycle I (60%), Cycle II (78%). Based on the results of the study, it can be concluded that the application of group investigation cooperative learning with gadget media in Indonesian language learning can increase student activity in class XI Science 4 State High School 1 Wajo.